Evaluation of low temperature tolerance in irrigated rice (Oryza sativa L.) genotypes at reproductive phase in a field experiment, during a spontaneous climatic event in the 2019/2020 crop season - Marschalek, Rubens; Oliveira, Douglas George de; Souza, Natalia Maria de; Facchinello, Paulo Henrique Karling; Terres, Laerte Reis; Sangoi, Luis (Revista de Ciências Agroveterinárias, 2023)
Concerning the occurrence of a spontaneous event of low temperatures (<17 oC), in an irrigated rice field experiment, during the reproductive phase of the crop, yield was evaluated as well as percentage of grain sterility and number of panicles. The experiment was conducted in the south of Santa Catarina, in the 2019/2020 crop season, having been water-seeded in randomized blocks with three replications. Of the total number of genotypes that made up the experiment, 13 were selected to make up the main analysis, of sterility. Based on a series of previous studies for stress due to low and high temperatures, the hypothesis was that the SC 806 line would stand out as resilient. Based on a series of previous studies for low and high temperature stress, the hypothesis was that the SC 806 inbreed line would stand out as resilient. In fact, SC 806 showed significantly lower sterility levels than the commercial controls, SCS116 Satoru, SCS122 Miura and SC 790 (SCS125), while remaining competitive in terms of yield. Thus, SC 806 confirmed its resilience to low temperatures, what was a behavior showed in previous experiments, proving to be promising as a candidate for release as cultivar soon.